Kesadaran Body Positivity Dalam Film Imperfect - Larasati, Ukhti Tri; Hamzah, Radja Erland; Saifulloh, Muhammad (Prisani Cendekia Institute, 2025)
The phenomenon of self-acceptance or self-love is increasingly relevant in today's society. The beauty standards formed in the community often lead individuals to feel less confident about themselves, which can negatively impact their self-image. In response to this issue, the concept of body positivity has emerged as a form of self-acceptance and a positive view of one's own body. These body positivity values are disseminated through various mass media, including films. The film